Commercial Bribery: Issues of Criminal Liability Classificationand Problems of Qualification - I. G. Ragozina (Сибирское юридическое обозрение, 2019)
The article considers the issue of classifying degrees of criminal liability for commercial bribery, depending the bribe amount. It also analyses problematic qualification issues arising in connection of with determination of criminal liability for mediation in commercial bribery, taking into account the position of the executors of law. According to the Author, the absence of indication of liability for mediation in small-scale commercial bribery in Art. 2041 of the Criminal Code of the Russian Federation led to unreasonable decriminalization of such actions. The paper studies the issue of possible application of compliance investigation procedure in solving the question of criminal liability for mediation in small-scale commercial bribery. On the basis of the research conducted by the Author, a suggestion is made regarding the need for amending the criminal law providing for liability for commercial bribery and mediation in it.